Mannheim Peritonitis Index (Mpi) Score as A Predictor of Outcome in Patients with Secondary Peritonitis - Joshi, Pravin; Poudel, Rajesh; Chandra, Kailash (Journal of Universal College of Medical Sciences, 2018)
INTRODUCTION: Secondary bacterial peritonitis from hollow viscous perforation is one of the common surgical emergencies and carries higher mortality. Several scoring systems are applied to predict the outcome of patients with perforation peritonitis. Mannheim Peritonitis Index (MPI) is one among many. Our aim of the study is to evaluate Mannheim peritonitis Index for predicting the outcome in patient with secondary bacterial peritonitis. MATERIALS AND METHODS: A retrospective study was conducted in the Department of General Surgery, Universal College of Medical Sciences, Bhairahawa from February 2012 to July 2013. All patients clinically diagnosed as peritonitis and who underwent laparotomy were included in the study. MPI score of all the study patients were calculated and categorized into three groups depending upon the score; less than 15, 15-25 and more than 25. Mortality of patients from each group was calculated and predictive value of each factor was determined. RESULTS: Total 60 patients were included in the study. Forty-four were male and sixteen were female. There were total five mortalities. All were of above 50 years age group. Patients beyond 50 years of age had a significantly higher (p = .005) probability of dying in the early post-operative period. MPI score more than 15 was not statistically significant (p = .06), patients with MPI more than 25 had more probability of dying, hazard ratio (HR 3.4 with 95% CI). Journal of Universal College of Medical Sciences (2016) Vol.04 No.02 Issue 14, page: 6-9